The Mural Paintings in St. Fosca's near Peroj (Istria) and Their Specific Place in the Context of European Romanesque - Maraković, Nikolina (Array, 2008)
The paper deals with one of the most significant examples of Romanesque mural painting in Croatia. Despite the fact that it has been in the focus of resesrch for over half a century, it has still not got a deserved monographic study. The paintings' iconography and style are analysed, which may contribute to redefining their place in European Romanesque painting, and provide a clearer insight into their quality, originality and uniqueness. The monumental decoration of a rural church thus becomes a monument of primary importance in explaining and understanding some of the most important features of European Romanesque art.